Modelling the information-seeking behaviour of international students in their use of social media in Malaysia - Bukhari, Sarah; Hamid, Suraya; Ravana, Sri Devi; Ijab, Mohamad Taha (University of Boras, 2018)
Introduction. The understanding of the information-seeking behaviour of international students using social media is limited. Therefore, the purpose of this research is to model the information-seeking behaviour of international students when they use social media to find information. Method. A mixed method approach was employed to collect data from the literature. Semi-structured interviews were conducted with twenty international students of different demographic backgrounds and with eleven staff members who work with international students. Questionnaires were distributed to 205 international students from four universities in Malaysia. Analysis. Using the literature review and empirical data, we propose a model of the information-seeking behaviour of international students who use social media, as validated and verified from the questionnaire. Results. The information-seeking activities were identified as informal searching, deciding, interacting, following, verifying and saving. The sources were search engines, social media and face-to-face settings. However, social media are more dominant than search engines and face-to-face communication. The questionnaire validated the proposed model and demonstrated that demographic variables exert a significant effect on the information-seeking behaviour of international students as they use social media. Conclusion. This research enhances the previous models of information-seeking behaviour by adding the role of social media and provides valuable insights for international students, universities and higher-education institutions.